Optimized method for isolating highly purified and functional porcine aortic endothelial and smooth muscle cells. Issue 11 (18th April 2017) - Beigi, Farideh; Patel, Mitalben; Morales‐Garza, Marco A.; Winebrenner, Caitlin; Gobin, Andrea S.; Chau, Eric; Sampaio, Luiz C.; Taylor, Doris A.
Abstract : Numerous protocols exist for isolating aortic endothelial and smooth muscle cells from small animals. However, establishing a protocol for isolating pure cell populations from large animal vessels that are more elastic has been challenging. We developed a simple sequential enzymatic approach to isolate highly purified populations of porcine aortic endothelial and smooth muscle cells. The lumen of a porcine aorta was filled with 25 U/ml dispase solution and incubated at 37°C to dissociate the endothelial cells. The smooth muscle cells were isolated by mincing the tunica media of the treated aorta and incubating the pieces in 0.2% and then 0.1% collagenase type I solution. The isolated endothelial cells stained positive for von Willebrand factor, and 97.2% of them expressed CD31. Early and late passage endothelial cells had a population doubling time of 38 hr and maintained a capacity to take up DiI‐Ac‐LDL and form tubes in Matrigel®. The isolated smooth muscle cells stained highly positive for alpha‐smooth muscle actin, and an impurities assessment showed that only 1.8% were endothelial cells. Population doubling time for the smooth muscle cells was ∼70 hr at passages 3 and 7; and the cells positively responded to endothelin‐1, as shown by a 66% increase in the intracellular calcium level. This simple protocol allows for the isolation of highly pure populations of endothelial and smooth muscle cells from porcine aorta that can survive continued passage in culture without losing functionality or becoming overgrown by fibroblasts. Abstract : Isolating pure populations of endothelial and smooth muscle cells from large elastic mammalian vessels remains a challenge in vascular biology. A sequential enzymatic approach to isolate highly purified populations of porcine aortic endothelial and smooth muscle cells has been established. This simple protocol allows for the isolation of highly pure populations of endothelial and smooth muscle cells from porcine aorta that can survive continued passage in culture without losing functionality or becoming overgrown by fibroblasts.